INTERPERSONAL METAFUNCTIONS IN L2 JOURNALISM: TENOR AND MODALITY ANALYSES OF EFL STUDENTS’ SOFT NEWS - Zulfikar Zulfikar; Amrizal Amrizal; Teuku Zulfikar; Mohamad Syafri (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
This study investigates how interpersonal meaning is constructed in EFL students’ soft news writing through the lens of Systemic Functional Linguistics. Drawing on a qualitative descriptive design, the research analyzed a corpus of eleven student-produced soft news articles written by Indonesian undergraduate EFL learners. The analysis focused on two complementary dimensions of interpersonal meaning: the socio-semiotic variable of tenor and the lexicogrammatical system of modality. Tenor analysis revealed that the students generally position themselves appropriately as reporters or chroniclers, maintaining a formal yet empathetic relationship with a generalized readership and adopting affective stances consistent with the human-interest orientation of soft news. At the grammatical level, modality analysis showed a strong preference for implicit, objective modalization with low to median values of probability and usuality, reflecting journalistic caution and an emerging awareness of neutrality. In contrast, modulation is used infrequently and displays a polarized distribution, with obligation realized either weakly or strongly and inclination largely restricted to low values. This asymmetry suggests that while students demonstrate greater control over epistemic positioning, they show more limited ability to negotiate interpersonal pressure and reader alignment. The findings highlight the pedagogical value of SFL-informed instruction in helping EFL learners connect contextual awareness with linguistic realization and develop more flexible control of interpersonal resources in journalistic writing.